The perception performance of visual signal stimuli when their density is changing - Penkauskas, A. (Psichologija, 1965)
The paper was intended to investigate the effectiveness of visual stimuli signal perception while their density field is changing.The study was performed using the response time measurement method. The density constant in the field of vision and visual field size were changed in the experiment.The study showed that the perception of effectiveness decreased with increasing visual stimuli signal density, while when the density decreases it increased. Optimum and critical density were identified.Perception of visual signal stimuli, while changing its density, takes place directly in both grouping and counting.
Keywords: vision; visual signaling stimuli; perception; visual signal stimuli density